PERANCANGAN SEGMENTASI PELANGGAN BERDASARKAN VARIABEL RECENCY, FREQUENCY DAN MONETARY DENGAN PENDEKATAN CLUSTERING PADA UMKM MICHIKO SIRUP CIREBON - Dwi Apriyani, Intan
Michiko Syrup is a business that has a product known as Michiko Syrup and Juice which focuses on Mango Lip flavored drinks and syrups which are its flagship products. Michiko Syrup is also a regional beverage producer in Cirebon that not only contributes to significant local economic growth but also plays an important role in preserving traditional products, local culture, and creating jobs for the local community. Michiko Syrup has